Application of phosphorus amendments reduces metal uptake and increases yield of Oryza saliva L. (rice) in Cd/Cu-contaminated paddy field. (March 2023) - Wu, Jiahui; Song, Qingmei; Wu, Yingxin; Liu, Junjun; Wu, Zhuohao; Zhou, Jingyan; Wang, Yuntao; Wu, Wencheng
Abstract: To alleviate worldwide food safety issues caused by metal contamination, an easily available material is urgently needed for extensive application. In this study, calcium magnesium phosphate fertiliser (Pcm) was applied to a Cd/Cu co-contaminated paddy field in comparison with limestone and organic fertiliser. The results showed that only Pcm is effective in simultaneously reducing Cd uptake by 56.7% and Cu uptake by 36.2% in Oryza saliva L. (rice). The rice yield, reduced mainly by Cu, also increased by 30.1% with respect to the enhancement of soil pH, cation exchange capacity and availability of phosphorus, as well as the reduction in availabilities of Cd and Cu. Additionally, Pcm dramatically shaped the bacterial community structure, with Proteobacteria and Firmicutes predominant in the soils. The beneficial genera Exiguobacterium, Citrobacter, and Acinetobacter, which are vital for phosphate dissolution and Cd/Cu immobilisation, were also enriched. The results demonstrated that the application of Pcm at 0.4% (w:w) was able to enhance both crop quantity and quality in Cd/Cu co-contaminated paddy fields by reducing Cu/Cd availability, promoting rice yield, and reshaping bacterial community structures. Graphical abstract: Image 1 Highlights: Ca–Mg–P fertiliser (Pcm) enhances crop yield and quality from Cd/Cu-contaminated paddy field. Pcm increased 30.1% of rice yield, which had been mainly inhibited by Cu. Pcm reduced Cd and Cu in rice grain by 56.7% and 36.2%, respectively. Pcm enriches beneficial bacterial groups and consequently enhances soil ecofunction.